Penilaian Kolesterol Total dan HDL sebagai Deteksi Dini Risiko Penyakit Kardiovaskular pada Populasi Dewasa di Gereja Asisi Jakarta - Tantoso, Lidya; Santoso, Alexander Halim; Gunaidi, Farell Christian; Teguh, Stanislas Kotska Marvel Mayello; Gracienne Gracienne (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Hypercholesterolemia is a common metabolic condition found in the adult population and significantly contributes to the increased risk of cardiovascular diseases, such as coronary heart disease and stroke. This condition is often asymptomatic, making early detection of total cholesterol and HDL levels a crucial step in identifying the risk of atherosclerosis at an earlier stage. A screening program conducted at the Asisi Church revealed that out of 68 participants, 34 individuals (50%) had abnormal total cholesterol levels, while 10 individuals (14.71%) had very low HDL levels, and 33 individuals (48.53%) had low HDL levels. These findings emphasize the importance of routine lipid profile assessments to prevent more severe cardiometabolic complications. Through education on healthy eating patterns, increased physical activity, and better control of risk factors, the community is expected to maintain optimal lipid profiles and improve overall quality of life.